Legal Protection for Women and Children as Victims of Human Trafficking in Indonesia - Ni Putu Rai Yuliartini; Ida Bagus Wyasa Putra; Gede Marhendra Wija Atmaja; Dewa Gede Sudika Mangku (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: The background of this research is the existence of problems related to legal protection policies for women and children who are victims of human trafficking in Indonesia. Based on data from the Ministry of Foreign Affairs, it is known that there were 35 victims of human trafficking in 2010, while in 2011 and 2012, there were 33 people and 92 people, respectively. One of the policies made by the government regarding the above problems is Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. However, it is found that this law has not been able to reduce human trafficking in Indonesia. In addition, this law is considered ineffective in fulfilling the rights of victims in which the criminal law's provision of protection to victims of human trafficking has not yet produced a clear pattern.Purpose/Objective Study: This study aims to analyze the legal protection for women and children as victims of human trafficking in Indonesia.Design/Methodology/Approach: This research is normative legal research (juridical normative) which uses a statute approach and a conceptual approach related to legal protection for women and children victims of human trafficking in Indonesia. Research results are further associated with the values contained in Human Rights.Findings: Based on the description above, the problems found are as follows: The number of cases of human trafficking in Indonesia continues to increase; Legal protection efforts for women and children victims of human trafficking viewed from a human rights perspective in Indonesia have not been effective; The form of protection for victims of human trafficking by criminal law has not yet shown a clear pattern.Paper Type: Research Article